User-centered design : A key to contract simplification - Finnegan, Milva (Vaasan yliopisto, 2021)
Contracts are a vital part of business-to-business (B2B) exchanges. They guide the exchange relationship and define its terms. A challenge that companies face is the complexity of contract documents. Traditional documents, consisting of black and white text without clear headings or paragraph breaks are difficult to read and comprehend. Contracts are not user friendly. Consequently, businesses spend extensive time and resources on contract negotiations, drafting and reviewing. In B2B transactions, contracts are multi-user and cross-functional documents supporting both business and legal objectives. In order for contracts to serve as effective communication tools, their design needs to consider all users. This dissertation aims to find solutions for how design thinking can be leveraged to reduce complexity and make contracts more user friendly. The research is based on relational contract theory, proactive contracting, and user-centered design research. The work studies contract operations as part of business and society, using a mixed-method approach comprised of both qualitative and quantitative research. A user-centered design process for contract development is presented as a framework in Chapters 1 and 2, and three distinct document design categories—structure, language, and visualization—are selected as the primary focus areas for the research. Chapter 3 discusses structure simplification that focuses on how to categorize, layer, and organize information. I propose a user-based categorization and a contract building blocks approach as part of the solution. Chapter 4 focuses on the written language of contracts, presenting the idea of a Controlled Contract Language (CCL). Chapter 5 examines how visualization can reduce the reader’s cognitive load of processing complex contract information. The overall aim of the dissertation is to provide both a theoretical and a practical contribution toward creating simplified contract documents.

Sopimukset ovat keskeinen osa yritysten liikesuhteita. Sopimukset ohjaavat liiketoimintaa ja määrittelevät sen ehdot. Sopimusten monimutkaisuus on yrityksille haasteellista. Perinteiset sopimukset ovat mustavalkoista tekstiä, niissä ei ole selviä otsikoita tai kappalejakoa, ja ne ovat vaikeita lukea ja ymmärtää. Sopimukset eivät ole käyttäjäystävällisiä. Tästä seuraa, että yritykset kuluttavat paljon aikaa ja resursseja sopimusten neuvottelemiseen, laatimiseen ja arviointiin. Yritysten välisiä sopimuksia käyttävät useat eri käyttäjät ja toiminnot. Sopimusten rooli on tukea liiketoiminnallisten ja oikeudellisten tavoitteiden saavuttamista. Jotta sopimukset toimivat tehokkaina viestintävälineinä, niiden muotoilussa tulisi huomioida kaikki käyttäjät. Tämän väitöskirjan tavoitteena on löytää ratkaisuja siihen, miten muotoiluajattelua voidaan hyödyntää vähentämään monimutkaisuutta ja tuottamaan käyttäjäystävällisempiä sopimuksia. Tutkimuksen teoreettisena viitekehyksenä toimivat relationaalinen sopimusteoria, ennakoiva sopiminen, sekä käyttäjälähtöinen muotoilututkimus. Tässä työssä tutkitaan sopimustoimintoja osana liiketoimintaa ja yhteiskuntaa. Tutkimus yhdistää sekä laadullisia että määrällisiä tutkimusmenetelmiä. Käyttäjäkeskeinen sopimusmuotoiluprosessi esitetään lähtökohtana luvuissa 1 ja 2, joissa on valittu tutkimuksen pääkohteiksi kolme asiakirjamuotoilun osa-aluetta: rakenne, kieli ja visualisointi. Luku 3 käsittelee rakenteen yksinkertaistamista, joka keskittyy siihen, miten tietoa voidaan luokitella, järjestää ja kerrostaa. Johtopäätöksenä esitetään käyttäjäpohjaista luokittelua ja sopimuksen rakentamista osina. Luku 4 keskittyy sopimusten kirjoitettuun kieleen ehdottaen, että sopimuksille luotaisiin oma kontrolloitu kieli. Luku 5 tarkastelee visualisointia keinona vähentää monimutkaisen sopimussisällön käsittelyyn liittyvää lukijan kognitiivista kuormitusta. Väitöskirjan kokonaistavoitteena on tuottaa sekä teoriaa että käytäntöä palvelevia tuloksia yksinkertaisempien sopimusasiakirjojen tuottamiseen.
Käyttäjälähtöinen muotoilu : Tie sopimusten yksinkertaistamiseen
Keywords: agreements; user-centered design; contract law; fi=Talousoikeus|en=Business Law|